Simulated Dynamics of Mixed Versus Uniform Grain Size Sediment Pulses in a Gravel‐Bedded River. Issue 10 (13th October 2021) - Ahammad, Muneer; Czuba, Jonathan A.; Pfeiffer, Allison M.; Murphy, Brendan P.; Belmont, Patrick
Abstract: Mountain rivers often receive sediment in the form of episodic, discrete pulses from a variety of natural and anthropogenic processes. Once emplaced in the river, the movement of this sediment depends on flow, grain size distribution, and channel and network geometry. Here, we simulate downstream bed elevation changes that result from discrete inputs of sediment (∼10, 000 m 3 ), differing in volume and grain size distribution, under medium and high flow conditions. We specifically focus on comparing bed responses between mixed and uniform grain size sediment pulses. This work builds on a Lagrangian, bed‐material sediment transport model and applies it to a 27 km reach of the mainstem Nisqually River, Washington, USA. We compare observed bed elevation change and accumulation rates in a downstream lake to simulation results. Then we investigate the magnitude, timing, and persistence of downstream changes due to the introduction of synthetic sediment pulses by comparing the results against a baseline condition (without pulse). Our findings suggest that bed response is primarily influenced by the sediment‐pulse grain size and distribution. Intermediate mixed‐size pulses (∼50% of the median bed gravel size) are likely to have the largest downstream impact because finer sizes translate quickly and coarser sizes (median bed gravel size and larger) disperse slowly. Furthermore, a mixed‐size pulse, with a smaller median grain size than the bed, increases bed mobility more than a uniform‐size pulse. This work has important implications for river management, as it allows us to better understand fluvial geomorphic responses to variations in sediment supply. Plain Language Summary: Sediment often enters mountain rivers from a variety of natural and human sources. Here, we simulate how this added sediment results in downstream changes in the amount of sediment in the river channel. This work was applied to a 27 km section of the Nisqually River, Washington, USA. We compare observed changes in the level of the stream bottom and accumulation rates in a downstream lake to model results. Then we investigate the magnitude, timing, and persistence of downstream changes due to the introduction of added sediment by comparing the changes against a baseline condition (without the added sediment). We found that added sediment particles that are half as large as on the riverbed and with a range of sizes are likely to have the largest downstream impact because smaller sizes move quickly and larger sizes move slowly. Furthermore, added sediment particles that are smaller than on the riverbed and with a range of sizes help more sediment particles on the riverbed move than if that sediment addition all had the same particle size. This work has important implications for river management, as it allows us to better understand how rivers are affected by variations in added sediment. Key Points: Channel incision may occur instead of aggradation when pulse volume is relatively small and pulse grain size is finer than bed Intermediate grain size pulses have the largest downstream effects; finer sizes translate quickly and coarser sizes disperse slowly A mixed‐distribution pulse with smaller median grain size than the bed increases bed mobility more than a uniform‐distribution pulse